Multiple impact assessment and water quality based on diatom, benthic invertebrate and fish communities in the Arieș River catchment area (Transylvania, Romania) - Karina Paula BATTES; Mirela CÎMPEAN; Laura MOMEU; Anca AVRAM; Klaus Werner BATTES; Ionuț Viorel STOICA (Studia Universitatis Babeș-Bolyai. Biologia, 2018)
The present paper represents an assessment of human impacts affecting the Arieș River catchment area, a region heavily affected by the mining  industry documented in the middle river course (Roșia Montană, Abrud, Roșia Poieni) since the Roman period. Other important impacts in the study area were: eutrophication / organic pollution due to discharges of untreated domestic wastes of villages and towns from the region; river regularization works, wood exploitation and processing facilities and industrial wastes downstream Turda and Câmpia Turzii localities. Water quality evaluation was carried out using river biotic communities recommended by the European legislation (Water Framework Directive, WFD): diatoms, benthic invertebrates and fish. Twenty-three sampling sites were considered along the Arieș River main course and its main tributaries, and standardized methods were employed for sampling and processing of biological data. Benthic invertebrates prooved to be the most sensitive community, indicating disturbed ecological status downstream the mining-affected region mainly due to high contamination of river sediments. While ichthyofauna responses were moderate (with water quality classes usually ranging from high to moderate), diatoms reflected better the effects of eutrophication / organic pollution caused by human settlements.